Professional Nurses Engagement in Non‐Nursing Work? An Examination of Reasons and Outcomes. - Fitzpatrick, Joyce J. (Journal of Nursing Scholarship, 2026)
Purpose: To critically examine the effect on professional nurses' engagement in non‐nursing tasks on nurse, patient, and organizational outcomes. Background: Research undertaken in several countries indicates that a significant amount of nurses' time is spent in non‐direct nursing care, often in non‐nursing tasks. Negative outcomes of professional nurses' time spent on non‐nursing tasks have been identified, including missed nursing care and burnout and turnover among nurses. Challenges for change in care delivery are addressed. Conclusions: There are multiple opportunities for workforce redesign, including extending the applications of technology in care delivery. Nurse leaders and professional nurses must seize opportunities to engage in solutions to current challenges of nursing work, particularly within hospitals, to focus professional nursing work directly on patient care that leads to optimal health outcomes. Clinical Relevance: Reducing the non‐nursing work for clinical nurses will reduce the overall workload and potentially lead to positive nurse and patient outcomes.